2017
DOI: 10.2174/1871526517666170117111350
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Adverse Drug Reactions to Highly Active Antiretroviral Therapy (HAART) among HIV Positive Patients in Imam Khomeini Hospital of Tehran, Iran

Abstract: Given the high prevalence of adverse drug reactions among HIV positive patients taking antiretroviral therapy (ART) in this study, clinicians should be aware of ADRs at the initiation of ART as complications can affect patients' adherence to the therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Adverse effects of ARVs are related to each compound as well as to the genetic factors of the host and the patient's lifestyle. In a study by Golrokhy et al (Golrokhy et al, 2017 ) 94% of ART exposed patients exhibited adverse effects. The discomfort created by various side effects is an important factor that diminishes the adherence or leads to treatment discontinuation.…”
Section: Barriers To Artmentioning
confidence: 99%
“…Adverse effects of ARVs are related to each compound as well as to the genetic factors of the host and the patient's lifestyle. In a study by Golrokhy et al (Golrokhy et al, 2017 ) 94% of ART exposed patients exhibited adverse effects. The discomfort created by various side effects is an important factor that diminishes the adherence or leads to treatment discontinuation.…”
Section: Barriers To Artmentioning
confidence: 99%
“…[13] Several studies have also reported from Iran on epidemiological characteristics (occurrence, prevalence, or incidence) of DRPs, especially ADRs, which have emphasized on the active role of clinical pharmacists in decreasing these types of problem. [14151617181920212223] However, it should be noted that all of these studies have been conducted by clinical pharmacists themselves and in their employment centers, which may indicate a source of probable bias.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a cross-sectional survey in Iran from 2009 to 2010 conducted by [27] among 200 patients who were HIV positive to find out the prevalence of adverse drug reactions among them while they take their ART. The result showed that 188 of the participants experienced diverse side effects of ART which led to reduced adherence to therapy while some discontinued treatment.…”
Section: Resultsmentioning
confidence: 99%